Another technology transforming the Music Industry : Blockchain - Marques, Miguel Carvalho (2019)
The blockchain is an emerging technology, receiving increased attention due to its applicability in several different areas of business, among other reasons. One of the possible applications of blockchain is in the music industry. New ventures exploring this subject have been appearing, offering a range of different solutions to some of the most pressing issues in the industry. Past literature focused on the technology and how its specificities can help in changing a culture of lack of transparency and inefficiency in the revenue streams, ultimately harming the artists. This study starts by providing a detailed picture of the music industry, their several actors, their functions and relationships, only then framing blockchain in this network. By collecting insights from different players in the music industry, positioned along the value chain and with heterogenous interests, the research goes further in understanding their vision on the industry. It is learned that there are two contrasting dimensions in it, one of which is seemingly more accessible to the new platforms. Moreover, the pain points identified are confirmed by the music community, even though other issues seem to be more critical. Considering this, the level of attractiveness of the industry for the blockchain projects is assessed and a new limitation to its market penetration is discovered: the lack of knowledge on the subject existing in the music community today. Still, its impact is estimated by providing a new image of the possibly reorganized music industry supply chain.